2009
DOI: 10.1095/biolreprod.108.072215
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 Gene Promoter Polymorphisms in Women with Pregnancy Loss: Preferential Association with Embryonic Wastage1

Abstract: Interleukin 10 (IL10) is associated with maternal immunotolerance. IL10 also down-regulates decidual cell tissue factor expression, the main molecule triggering coagulation activation: this antithrombotic effect may protect the umbilicoplacental vasculature from the 10th wk of gestation onward. IL10 down-regulation may thus dispose to early pregnancy loss (PL) due to maternal immunotolerance defect or late pregnancy failure due to placental vascular insufficiency. IL10 gene promoter polymorphisms associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
0
13
0
4
Order By: Relevance
“…We were able to eliminate genotyping error; therefore, we believe HWE violation was due to a biased sample of women who delivered preterm infants, which enriched for the alleles under investigation. The SNPs included in this study have been implicated in a variety of obstetrical complications including SGA (rs2070874 and rs2243250; Engel et al, 2005), spontaneous preterm birth (rs1800795; Wu et al, 2013), and pregnancy loss (rs1800871 and rs1800872; Cochery-Nouvellon et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to eliminate genotyping error; therefore, we believe HWE violation was due to a biased sample of women who delivered preterm infants, which enriched for the alleles under investigation. The SNPs included in this study have been implicated in a variety of obstetrical complications including SGA (rs2070874 and rs2243250; Engel et al, 2005), spontaneous preterm birth (rs1800795; Wu et al, 2013), and pregnancy loss (rs1800871 and rs1800872; Cochery-Nouvellon et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is a regulatory cytokine, and SNPs in the promoter region of the IL10 gene are associated with IL-10 levels (Capasso et al, 2007; Lowe, Galley, Abdel-Fattah, & Webster, 2003; Qaddourah et al, 2014; Yilmaz, Yentur, & Saruhan-Direskeneli, 2005). Maternal IL10 genetic variation has been associated with pregnancy loss (Cochery-Nouvellon et al, 2009; Qaddourah et al, 2014), perhaps due to the role of IL-10 in maintaining maternal–fetal tolerance (Denney et al, 2011). …”
mentioning
confidence: 99%
“…1, 49 articles were excluded, of which 32 were duplicate ones and 17 with no relation to this topic. The remaining 17 studies were full-text reviewed, and five studies were excluded, among which, one was not about recurrent abortion and not a case-control study [13], two were of unavailable genotype [32,33] and the other two were metaanalysis [25,26]. Finally, in the current study, 12 eligible case-control studies that meet the inclusion criteria were included in our meta-analysis [14,16,17,[19][20][21][22][23][24][34][35][36].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Several studies have identified single-nucleotide polymorphisms (SNPs) of IL-10 gene can significantly influence the levels of IL-10 production and key obstetric complications, particularly the promoter variants control IL-10 secretion [13][14][15]. Though a number of studies have been conducted to investigate the association between promoter polymorphisms of IL-10 with RPL, the results are not consistent [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Известно, что IL-10 принимает активное учас-тие в обеспечении иммунотолерантности материнского организма к развивающемуся зародышу. Кроме того, IL-10 обеспечивает снижение уровня экспрессии деци-дуальными клетками ряда молекул -активаторов коа-гуляции (Cochery-Nouvellon et al, 2009). Наличие в ге-нотипе аллелей -31 Т гена IL-1β или -592 А гена IL-10 предполагает повышение уровня провоспалительных цитокинов в тканях-мишенях.…”
Section: обсуждение результатовunclassified